Uterine perfusion in patients with MMP2 gene polymorphisms - Tatiana E. Filipenkova; Liia N. Shcherbakova; Aleksandr V. Balatskiy; Larisa M. Samokhodskaya; Olga B. Panina (IP Berlin A.V., 2021)
Aim. To investigate the effect of allelic polymorphisms of the MMP2 gene on uterine perfusion in patients planning pregnancy. Materials and methods. 95 women planning pregnancy were examined. The patients underwent clinical and laboratory examination, analysis of single nucleotide polymorphisms rs2285052 and rs243865 of the MMP2 gene, ultrasound examination on days 1825 of the menstrual cycle with an assessment of the pulsatility index of blood flow of the uterine vessels and a qualitative assessment of endometrial and subendometrial perfusion. Depending on the genotype, the patients were divided into 3 groups: first with haplotype rs2285052(A)rs243865(T), second with haplotype rs2285052(A)rs243865(С), and a third control group with rs2285052(С/С)rs243865(С/С) genotype. Results. Decreased perfusion in the subendometrial zone was found in 40.6, 44.4 and 19.4% of patients in the 1, 2 and 3 groups, respectively; decreased perfusion of endometrium in 68.8, 55.6 and 36.1% of patients in the 1, 2 and 3 groups, respectively. Spiral arteries were not visualized in 28.1, 14.8 and 11.1% of patients in the 1, 2 and 3 groups, respectively. No statistical differences were found in the pulsatility index of uterine blood flow depending on the genotype. Conclusion. In patients with the A rs2285052 and T rs243865 alleles of the MMP2 gene poor vascular patterns of the endometrium and subendometrial zone of the uterus were statistically significantly more frequent, which can lead to infertility. These associations are more pronounced for the rs2285052 polymorphism. The simultaneous determination of the rs2285052 and rs243865 polymorphisms does not provide additional information compared to the definition of rs2285052 alone.